Pathways of retinoid synthesis in mouse macrophages and bone marrow cells. Issue 6 (14th January 2016) - Niu, Haixia; Hadwiger, Gayla; Fujiwara, Hideji; Welch, John S.
Abstract : Primary hematopoietic cells express Aldh3b1 and Aldh1a1, enzymes, which synthesize ATRA from vitamin A, yet do not synthesize intracellular ATRA in vivo. Abstract : In vivo pathways of natural retinoid metabolism and elimination have not been well characterized in primary myeloid cells, even though retinoids and retinoid receptors have been strongly implicated in regulating myeloid maturation. With the use of a upstream activation sequence‐GFP reporter transgene and retrovirally expressed Gal4‐retinoic acid receptor α in primary mouse bone marrow cells, we identified 2 distinct enzymatic pathways used by mouse myeloid cells ex vivo to synthesize retinoic acid receptor α ligands from free vitamin A metabolites (retinyl acetate, retinol, and retinal). Bulk Kit + bone marrow progenitor cells use diethylaminobenzaldehyde‐sensitive enzymes, whereas bone marrow‐derived macrophages use diethylaminobenzaldehyde‐insensitive enzymes to synthesize natural retinoic acid receptor α‐activating retinoids (all‐trans retinoic acid). Bone marrow‐derived macrophages do not express the diethylaminobenzaldehyde‐sensitive enzymes Aldh1a1, Aldh1a2, or Aldh1a3 but instead, express Aldh3b1, which we found is capable of diethylaminobenzaldehyde‐insensitive synthesis of all trans ‐retinoic acid. However, under steady‐state and stimulated conditions in vivo, diverse bone marrow cells and peritoneal macrophages showed no evidence of intracellular retinoic acid receptor α‐activating retinoids, despite expression of these enzymes and a vitamin A‐sufficient diet, suggesting that the enzymatic conversion of retinal is not the rate‐limiting step in the synthesis of intracellular retinoic acid receptor α‐activating retinoids in myeloid bone marrow cells and that retinoic acid receptor α remains in an unliganded configuration during adult hematopoiesis.